Phosphorus fertilization of grasses with dairy processing waste materials and contributions of soil microorganisms towards phosphorus uptake - Á. Velasco-Sánchez; Y. Hu; S.G. Sommers; G.Y.K. Moinet; J.W. Van Groenigen; I. Trinsoutrot-Gattin; N. Bennegadi-Laurent (Geoderma)
Dairy processing waste (DPW) is one of the largest agro-industrial residues globally and has the potential of reducing the dependency on mineral phosphorus (P) fertilizers in grasslands. However, the agronomical value and the effects of DPW and the secondary materials produced from it on grass yields and soil microorganisms remains largely unexplored. In a 112-day greenhouse experiment, we evaluated the biomass production and P uptake of two grass species, grown on a loamy topsoil, with contrasting growth strategies (Lolium perenne L. fast-grower vs Dactylis glomerata L. slow-grower) and the effects on soil microorganisms under the fertilization of raw DPW sludge, and its secondary materials (ash and hydrochar). We compared the fertilized pots with a positive control with triple-superphosphate (TSP) and a negative control without P application. Our results showed that Olsen P and plant P concentrations were highest in the treatment with TSP after one month of application for both grass species. However, biomass production, P uptake and phosphorus use efficiency (PUE) were the greatest for sludge at day 112 for both species (56.39 ± 3.34 g pot−1, 0.20 g ± 0.02 P and 56.18 ± 12.44 %, n = 8). Ash and hydrochar resulted in lower biomass production than TSP and sludge and their PUE was low (< 20 %). Fungi and arbuscular mycorrhiza fungi PLFA markers were among the most important variables in explaining P uptake. The results of our study suggest that application of DPW sludge and soil’s fungal biomass can reduce the dependency on mineral P fertilizers in grassland.